Birthweight of term infants and maternal occupation in a prospective cohort of pregnant women. The ALSPAC Study Team. Issue 1 (January 1998) - Farrow, A; Shea, K M; Little, R E
Abstract : OBJECTIVE: To study the relation between birthweight of term infants and maternal occupation. METHODS: Information on job titles since the age of 16, and sociodemographic and other lifestyle factors were obtained by means of questionnaires as part of the Avon longitudinal study of pregnancy and childhood (ALSPAC), from a cohort of 14, 000 pregnant women. The British 1990 standard occupational classification was used to code jobs within nine major job groups. RESULTS: For 9282 women who delivered term infants and reported a job for the relevant period, there was a significant difference in mean birthweight among the nine major job groups. A 148 g difference was found between the mean birthweight of infants born to women with professional occupations and those with plant and machine operative jobs. Multiple regression analysis adjusted for sex of infant, parity, maternal height, smoking, caffeine consumption, and race. After adjustment the maternal job was no longer significantly associated with birthweight. CONCLUSION: Despite the absence of a significant association between birthweight and job after adjustment, there were several findings which agreed with publications on maternal occupation and pregnancy outcome. The major job groups with the lowest birthweights included the following jobs; metal forming or welding, electric or electronic work, jobs in the textile trade, and assembling and working with equipment (mobile and stationary). The lack of an association may indicate that the study was of insufficient power to detect a small difference; it may indicate the presence of confounding variables that were not adjusted for or it may indicate that no association exists.